2014
DOI: 10.1111/jvim.12314
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Diseases and Conditions in Cats with Renal Infarcts

Abstract: BackgroundRenal infarcts identified without definitive association with any specific disease process.ObjectiveDetermine diseases associated with diagnosis of renal infarcts in cats diagnosed by sonography or necropsy.Animals600 cats underwent abdominal ultrasonography, necropsy, or both at a veterinary medical teaching hospital.MethodsInformation obtained from electronic medical records. Cats classified as having renal infarct present based on results of sonographic evaluation or necropsy. Time‐matched case‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Three studies (LOE 2–4, Good‐Fair) strongly support the association of feline cardiomyopathy with ATE . The cumulative risk of ATE at 1, 5, and 10 years was 3.5%, 9.5%, and 11.3%, respectively, in cats with hypertrophic cardiomyopathy or hypertrophic obstructive cardiomyopathy compared to 0.0%, 0.4%, and 0.7%, respectively, in apparently healthy cats (LOE 2, Good) .…”
Section: Guidelinesmentioning
confidence: 72%
“…Three studies (LOE 2–4, Good‐Fair) strongly support the association of feline cardiomyopathy with ATE . The cumulative risk of ATE at 1, 5, and 10 years was 3.5%, 9.5%, and 11.3%, respectively, in cats with hypertrophic cardiomyopathy or hypertrophic obstructive cardiomyopathy compared to 0.0%, 0.4%, and 0.7%, respectively, in apparently healthy cats (LOE 2, Good) .…”
Section: Guidelinesmentioning
confidence: 72%
“…Another study of 309 cats with renal infarcts found that these cats were 8 times more likely to experience distal ATE compared to time matched controls, and as well as a positive association between renal infarcts, HCM and ATE. These findings support feline HCM as a risk factor for thrombosis (LOE 4, Good) . In a third prospective case‐controlled study, cats with spontaneous echocontrast or atrial thrombi met the laboratory criteria for hypercoagulability, further supporting a hypercoagulable state in cats with cardiac disease (LOE 2, Good) …”
Section: Peco Question: Cardiac Disease In Catsmentioning
confidence: 96%
“…A hyperechoic renal segmental cortical lesion was observed in 1 MSC‐injected cat 1 week after injection, which was assumed to be a renal infarct. These changes are incidentally encountered in cats in the clinical practice setting and have been observed more frequently in Ragdoll cats and cats with cardiomyopathy . In the MSC‐injected cat with the renal segmental cortical lesion in this study, no heart murmur was identified on cardiac auscultation.…”
Section: Discussionmentioning
confidence: 53%
“…These changes are incidentally encountered in cats in the clinical practice setting and have been observed more frequently in Ragdoll cats and cats with cardiomyopathy. 44,45 In the MSC-injected cat with the renal segmental cortical lesion in this study, no heart murmur was identified on cardiac auscultation. An echocardiogram was performed to investigate for cardiomyopathy at a recheck appointment 1 year after completion of this study and no abnormalities were noted within the heart by a board certified cardiologist.…”
Section: Discussionmentioning
confidence: 55%